The effect of ball modification on improving the learning outcomes of basketball passing participants - Aviludin, Aviludin; Kurniawan, Fajar; Bastian, Risa Herdiyana (Universitas Tanjungpura, 2022)
This research is motivated by the low ability of students to pass basketball effectively, which has an impact on less than optimal learning outcomes in physical education learning. One of the factors identified was the lack of variety in learning media, particularly aids such as balls. Therefore, this study aims to determine the effect of ball modification on basketball passing learning outcomes in grade VII students of SMP Negeri 5 Cirebon City. The method used in this study is a quasi-experiment with a Nonequivalent Control Group Design. The research subjects consisted of two classes, namely the experimental class that was treated using a modified ball (volleyball) and a control class that continued to use a standard basketball. The data collection technique was carried out through a practical test of passing ability, including chest pass, bounce pass, and overhead pass. The results showed a significant increase in learning outcomes in the experimental group compared to the control group. The average post-test score of the experimental group reached 92.00, while the control group was only 82.97. Statistical analysis using the t-test showed a significance value (Sig.) of 0.000 < 0.05, which means that there is a significant difference between the two groups. Thus, the use of modified balls has been proven to be effective in improving basketball passing learning outcomes. This study concludes that the application of modified aids in physical education learning can be an innovative and efficient alternative strategy in improving students' motor skills, especially in big ball games such as basketball.